The role of social and physiological variables on older adults’ cognitive improvement after a group singing intervention: The Sing4Health Randomized Controlled Trial - Galinha, I. C.; Pinal, D.; Lima, M. L.; Labisa-Palmeira, A. (Psychosocial Intervention, 2021)
Population aging prompts efforts to help older adults maintain a high quality of life and independence. Group singing (GS) has shown benefits on social, physical, and cognitive domains, being a cost-effective strategy to reach these goals. Nevertheless, randomized controlled trials (RCT) evaluating systematic GS interventions and the interplay between their effects on those domains are scarce. Thus, the present RCT assessed whether a 34-session GS intervention boosts older adults’ cognitive functions (executive functions and verbal memory) and whether it has an impact on systemic inflammation markers. Additionally, it intended to determine whether changes in social or physiological domains mediated the intervention effects on cognition. One hundred and forty-nine participants were allocated to a waiting-list group, which kept their usual activity levels, or an intervention group. Blinded outcome assessments were conducted at baseline, post-intervention, and follow-up. Results confirmed positive effects of GS on cognition, especially marked for verbal memory. Evidence of GS’s protective effect on systemic inflammation is also provided. Mediation analyses revealed a complex interaction of GS intervention engagement and respiratory function and social wellbeing changes with the magnitude of cognitive improvement. These results highlight socialization and respiratory functions as critical pieces of multidimensional GS interventions, maximizing their benefits on older adults’ cognition.